2014
DOI: 10.1155/2014/475152
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Injection of SB203580 Inhibits the Inflammatory-Dependent Synthesis of Proinflammatory Cytokines in the Hypothalamus

Abstract: The study was designed to determine the effects of peripheral injection of SB203580 on the synthesis of interleukin- (IL-) 1β, IL-6, and tumor necrosis factor (TNF) α in the hypothalamus of ewes during prolonged inflammation. Inflammation was induced by the administration of lipopolysaccharide (LPS) (400 ng/kg) over 7 days. SB203580 is a selective ATP-competitive inhibitor of the p38 mitogen-activated protein kinase (MAPK), which is involved in the regulation of proinflammatory cytokines IL-1β, IL-6 and TNFα s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…RealTime RT-PCR was carried out with the use of the HOT FIREPol EvaGreen ® qPCR Mix Plus (Solis BioDyne; Tartu, Estonia) and HPLC-grade oligonucleotide primers (Genomed; Warszawa, Poland). The primer sequences were designed using Primer 3 software (Herman et al, 2014b) (Table 1). The relative gene expression was calculated using the comparative quantification option (Rasmussen, 2001) of the Rotor Gene 6000 software 1.7.…”
Section: Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…RealTime RT-PCR was carried out with the use of the HOT FIREPol EvaGreen ® qPCR Mix Plus (Solis BioDyne; Tartu, Estonia) and HPLC-grade oligonucleotide primers (Genomed; Warszawa, Poland). The primer sequences were designed using Primer 3 software (Herman et al, 2014b) (Table 1). The relative gene expression was calculated using the comparative quantification option (Rasmussen, 2001) of the Rotor Gene 6000 software 1.7.…”
Section: Assaysmentioning
confidence: 99%
“…Circulating inflammatory mediators acting both at the hypothalamic (Herman et al, 2014b) and pituitary level (Tsagarakis et al, 1998) play an important role in the induction of endocrine disorders during inflammation. Due to rich vascularization of the PT, the cells located in this pituitary region are an easy target for blood born inflammatory mediators such as interleukin-1 (IL-1β, IL1B for gene), interleukin-6 (IL-6, IL6 for gene) and tumor necrosis factor (TNF, TNF for gene) α which may affect the activity of cells located in the PT acting their corresponding receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this view, a study on microglial cells revealed that deletion of TLR2 and TLR4, as essential receptors in the induction of inflammation, prevented Aβ mediated P38 activation. On the other hand, specific inhibitor of P38 (SB203580) was shown to prevent the formation of Aβ mediated reactive oxygen species and phagocytosis (Reed-Geaghan et al, 2009[ 35 ]) and LPS-stimulated synthesis of pro-inflammatory cytokines (Herman et al, 2014[ 24 ]). These results clearly showed a reciprocal relationship between inflammation and P38 activation.…”
Section: Discussionmentioning
confidence: 99%
“…administration of the inhibitor SB203580 for 7 days abolished the 1.5-to two-fold increase in hypothalamic Il1b, Il6 and TNF expression after i.v. LPS injections (400 ng/kg BW) to anoestrous ewes (Herman et al, 2014). Even 1 h after i.v.…”
Section: Inflammatory Signalling To the Brain Via The Humoral Pathwaymentioning
confidence: 99%